2019
DOI: 10.1029/2019jf005225
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Monitoring Interval for Rockfall Magnitude‐Frequency Estimation

Abstract: Rockfalls commonly exhibit power law volume‐frequency distributions, where fewer large events are observed relative to more numerous small events. Within most inventories, the smallest rockfalls are the most difficult to detect and so may not be adequately represented. A primary challenge occurs when neighboring events within a single monitoring interval are recorded as one, producing ambiguity in event location, timing, volume, and frequency. Identifying measurement intervals that minimize these uncertainties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 59 publications
(93 reference statements)
6
63
0
1
Order By: Relevance
“…Following pointwise change detection, the data belonging to each individual rockfall event were grouped using the clustering algorithm DBSCAN (Density-Based Spatial Clustering of Applications with Noise), developed by Ester et al (1996). Contiguous points of change were assumed to belong to a single event, although the influence of rockfall scar coalescence has been recognized at intervals beneath the annual timescales used here (Barlow et al, 2012;Williams et al, 2019). DBSCAN is the most commonly used single-scan clustering technique and defines clusters based on the local density of points.…”
Section: Rockfall Identification and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Following pointwise change detection, the data belonging to each individual rockfall event were grouped using the clustering algorithm DBSCAN (Density-Based Spatial Clustering of Applications with Noise), developed by Ester et al (1996). Contiguous points of change were assumed to belong to a single event, although the influence of rockfall scar coalescence has been recognized at intervals beneath the annual timescales used here (Barlow et al, 2012;Williams et al, 2019). DBSCAN is the most commonly used single-scan clustering technique and defines clusters based on the local density of points.…”
Section: Rockfall Identification and Characterizationmentioning
confidence: 99%
“…We recognize that our distributions (captured annually), as opposed to previous local scale monitoring (captured monthly), could be prone to under-sampling and other biases, such as the threshold that was set for the minimum detectable change (0.10m) during data processing, as well as differences in the way that cloud-to-cloud comparison methods identify and treat insignificant change. Previous research has demonstrated the relative stability and reliability of power laws fit to rockfall volume probability distributions at monitoring intervals >12hours (Williams et al, 2019). We therefore consider that any bias in the data collected most likely relates to rockfalls that were not captured (e.g.…”
Section: Rockfall Magnitude Frequency and Erosionmentioning
confidence: 99%
See 2 more Smart Citations
“…High spatio-temporal resolution monitoring of rock cliffs using terrestrial laser scanning (TLS) point clouds (e.g., Abellán et al 2009Abellán et al , 2010Rosser et al 2013;Royán et al 2014Royán et al , 2015Kromer et al 2015aKromer et al , 2018Stock et al 2018) has shown that it is possible in some cases to detect precursor deformations below centimetric scale and to monitor them over time until failure. In addition to obtaining a more comprehensive rockfall inventory and a more realistic volume-frequency relationship (Barlow et al 2012;van Veen et al 2017;Williams et al 2018Williams et al , 2019, near real-time TLS surveys offer new opportunities to better anticipate failure (Eitel et al 2016;Kromer et al 2015bKromer et al , 2017. These systems also help to better understand the influence of environmental factors on rockfall triggering (Jaboyedoff and Derron 2005).…”
Section: Introductionmentioning
confidence: 99%